Research Competency and the Variables Affecting Successful Research: A Case Study of National Research Universities - Boonpen, Piyawan - (KASEM BUNDIT JOURNAL, 2018)
This qualitative research aimed to find the meaning of research competency and successful research, the conditions and factors contributing to research competency of researchers at National Research Universities. The results showed that the meaning of research competency covered 4 elements. The meaning of successful research consisted of 3 elements. The conditions and factors contributing to the successful research were: personal factors, workload and job demand, and organizational environment. The best conditions are integration of the three aspects.